Anime club in the public library - Žozefina Žentil Barić (Knjižnica)
Aim: The popularity of Japanese animation (anime) has increased worldwide in recent years. The paper aims to represent an anime club as an opportunity for public libraries to draw in young fans by offering them a place where they can exchange experiences and find like-minded peers. It reflects on the definition of anime and the reasons for its popularity, offers an insight into possible ways of using anime in public libraries and presents a case study of a successful anime club.